Nonlinear Optical Properties of CdSe and CdTe Core-Shell Quantum Dots and Their Applications - Kalsoom, Um e; Yi, Rongxing; Qu, Junle; Liu, Liwei (Frontiers in Physics, 2021)
The strong nonlinear optical behavior of low dimensional materials such as quantum dots and core-shell quantum dots had been a topic of intense research in recent years. As quantum dots have tunable emission via changes in their sizes, they are potentially useful in photo-electronics, photovoltaic nonlinear optics, light-emitting diode fabrication, and laser protections. Variation among core and shell shape, size along with the chemical composition of quantum dots define their enhanced nonlinear optical properties. Some specific nonlinear optical properties such as nonlinear refraction, optical limiting, saturable absorption, reverse saturable absorption of CdTe and CdSe QDs as well as core-shell QDs and their applications were assessed in this paper.